The rs5743836 polymorphism in TLR9 confers a population-based increased risk of non-Hodgkin lymphoma - Carvalho, Agostinho (2012)
We are grateful to Paulo Vieira, Cecília Leão, Manuel T. Silva, Nuno Sousa, Jorge Correia- Pinto, Joana Palha, Margarida Correia-Neves, Margarida Lima and Matthew Berry for all their input throughout these studies and critical reading of the manuscript. We are grateful to the patients who joint this study as well as to all members of the Life and Health Sciences Research Institute and School of Health Sciences, University of Minho, who contributed in any way to the development of this work